Changing farm sizes and farmers’ demographics in Ethiopia - Bachewe, Fantu Nisrane; Minten, Bart (International Food Policy Research Institute, 2023)
Important changes in farms and farm demographics are noted in Ethiopia since 2004/05. These changes have important implications on discussions of the future of Ethiopian agriculture. Comparing the national agricultural sample survey of the Ethiopian Statistical Services (ESS) data between 2004/05 and 2016/17, we find that: (1) Average farm sizes of smallholders declined by more than 10 percent over the decade, from 1.2 to 0.9 hectares; the decline in farm sizes of female headed households is more pronounced at over 21 percent, (2) Farmers are becoming older: the share of Ethiopian farmers under 35 declined from 36 to 30 percent, (3) The youth have smaller and declining farm sizes, declining from 0.9 to 0.8 hectares, (4) Rental markets are becoming more important, with 12 percent of crop land being rented in at the end of the period; especially the youth rely more on rental markets to access land, with 20 percent of their land rented in, and (5) Education levels are rapidly increasing, with the share of illiterate youth farmers declining from 56 to 30 percent. This has important implications for the future of Ethiopian agriculture and the overall economy.